Known to Us in this Great Absence: The Absent Self’s Identities in Edwin Muir’s Poetry - Tanvir, Muhammad Furqan (Journal of Research in Humanities, 2023)
This paper aims at exploring issues pertaining to the theme of an apparently absent self in Edwin Muir’s poetry, in the light of Derrida’s theory of metaphysics of presence. It offers a thorough deconstructionalist reading of some poems to highlight the suspension or negation of the privileging of presence over absence in the evaluation of being, the consequent redefinition of the self’s relationship with the other, and the ontological impossibility of envisaging unmediated nothingness. In other words, it demonstrates how Muir centralizes a liminal space between existence and nothingness in his treatment of the poetics of reality involved in the representation(s) of an absent self. As this process leads to the discovery of the loss of the transcendental signified, language fully reveals its reliance on provisional meanings.